Hubungan Penggunaan Media Sosial Dan Teman Sebaya Terhadap Perilaku Seks Pada Remaja Di SMA N 8 Kota Jambi - Assyafiah Harnum; Meinarisa Meinarisa; Fadliyana Ekawati (STIKes Ibnu Sina Ajibarang, 2023)
The use of social media and the influence of peers can provide a lot of information to adolescents, both information that is good for adolescent development or information that has a negative impact on these adolescents. To find out the relationship between the use of social media and peers on sexual behavior in adolescents at SMA N 8 Jambi City in 2023. The method used in this study is a quantitative method. Determination of the sample using Simple Random Sampling with the Slovin formula obtained n = 77 respondents who were taken proportionally based on each class. Primary data obtained from distributing questionnaires. Data analysis was carried out using Univariate and Bivariate Analysis. 71.43% of the use of social media in adolescents at SMA N 8 Jambi City is categorized as medium, 18.18% is categorized as low, and 10.39% is categorized as high. 58.44% of peer influence on adolescents at SMA N 8 Jambi City is categorized as moderate, 37.66% is categorized as low, and 3.9% is categorized as high. 84.42% of adolescent sexual behavior at SMA N 8 Jambi City is generally categorized as not at risk and 15.58% is categorized as at risk. There is a relationship between the use of social media on sexual behavior in adolescents at SMA N 8 Jambi City in 2023 which is seen based on the p-value of 0.030 which is smaller than 0.05. There is a relationship between social media and peers on sexual behavior in adolescents at SMA N 8 Jambi City in 2023 which is seen based on a p-value of 0.034, less than 0.05. There is a relationship between social media and peers on sexual behavior in adolescents at SMA N 8 Jambi City in 2023. It is hoped that schools can provide guidance for students and provide learning related to sexual behavior so that students do not get information on wrong sexual behavior. Thus, teenagers can be more careful in socializing so as not to fall into negative things that can damage their life and future.